1996
DOI: 10.1183/09031936.96.09101995
|View full text |Cite
|
Sign up to set email alerts
|

The expression of adhesion molecules in cigarette smoke-induced airways obstruction

Abstract: T Th he e e ex xp pr re es ss si io on n o of f a ad dh he es si io on n m mo ol le ec cu ul le es s i in n c ci ig ga ar re et tt te e s sm mo ok ke e--i in nd du uc ce ed d a ai ir rw wa ay ys s o ob bs st tr ru uc ct ti io on n Freshly resected lungs from heavy smokers with airways obstruction (n=10) and from heavy smokers with normal lung function (n=10) were collected in the operating room, inflated with optimal cutting temperature (OCT) medium and frozen over liquid nitrogen. Six micrometre thick cryosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
1
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 25 publications
3
23
1
2
Order By: Relevance
“…The evidence for this derives from studies demonstrating an increased number of inflammatory cells (10,14,19), their activation status (20), and the release of putative proinflammatory mediators (21). In our study we have demonstrated an increased number of leukocytes infiltrating the adventitia of pulmonary muscular arteries in COPD patients, largely constituted by activated T lymphocytes.…”
Section: Discussionmentioning
confidence: 56%
“…The evidence for this derives from studies demonstrating an increased number of inflammatory cells (10,14,19), their activation status (20), and the release of putative proinflammatory mediators (21). In our study we have demonstrated an increased number of leukocytes infiltrating the adventitia of pulmonary muscular arteries in COPD patients, largely constituted by activated T lymphocytes.…”
Section: Discussionmentioning
confidence: 56%
“…Furthermore, bloodflow through vessels subjects endothelial cells to shear stress, which can elicit cytoskeletal remodelling and activation of natural signalling cascades in endothelial cells, including the activation of nuclear factor-kB and upregulation of intracellular adhesion molecule (ICAM)-1 [15]. The flow-based assay used in the current study incorporates these aspects and, when used in conjunction with HUVEC, which have a similar adhesion molecule profile (following IL-1b stimulation) to that seen on bronchial post-capillary venules [10,11], provides an appropriate model of neutrophil-endothelial cell interactions in the airways of patients with COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were not used beyond their sixth passage. HUVEC were chosen for this study because of the ease of culture to confluence within the glass microslide, and the similar profile of adhesion molecule expression following interleukin (IL)-1b stimulation to that seen on postcapillary venules in the bronchial circulation of smokers [10,11].…”
Section: Study Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of macrophage associated antigen-1 (Mac-1) is increased on neutrophils of patients with stable COPD, suggesting that targeting such adhesion molecules may have therapeutic potential (Noguera et al 1998). The expression of leukocyte as well as epithelial/endothelial surface adhesion molecules was elevated in resected lung tissue from heavy smokers, consistent with an infl ammatory response to lung infl ammation but not correlated to the degree of airways obstruction (Gonzalez et al 1996). Increased levels of circulating intercellular adhesion molecule-1 (cICAM-1) and circulating E-selectin (c-E-selectin) in serum, and of cICAM-1 in BAL, were observed in COPD patients relative to controls.…”
Section: Adhesion Moleculesmentioning
confidence: 75%